Do environmental violations affect corporate loan financing? Evidence from China. Issue 7 (3rd October 2017) - Zou, Hailiang; Zeng, Saixing; Qi, Guoyou; Shuai, Ping
ABSTRACT: This article reports an empirical study suggesting that environmental violations generally have a negative influence on the level of loans that the violating firms hold in China and that after a violation announcement involving waste water discharge, firms are forced to take secured loans. These effects are found to be mitigated for state-owned firms and the media coverage of a certain violation event has a negative effect on the level of loans that firms obtain. Our work presents the evidence of a penalty mechanism in the credit market that fines firms for their environmental violations in a transition economy, and has some implications for business management and governmental policy.